Management to Increase the Effectiveness of Palliative Care for Cancer Patients - Kosoom, Kanta; Jarujittipant, Pisamai; Tanaborworpanid, Nutpatsorn (Arts of Management Journal, 2024)
The objectives of this study were to: 1) analyze the current conditions of palliative care for cancer patients; 2) study the expected and actual effectiveness of palliative care for cancer patients; 3) study the organizational characteristics affecting the effectiveness of palliative care for cancer patients; 4) study the characteristics of patient care and the readiness of management factors affecting the effectiveness of palliative care for cancer patients; and 5) analyze and suggest the guidelines for the management to increase the effectiveness of palliative treatment of cancer patients. Quantitative data was collected from doctors, nurses, and personnel who were responsible for palliative care for cancer patients, for a total of 558 people. In addition, qualitative data were collected from key informants among a total of 20 people. The data was analyzed using descriptive statistics, ANOVA and multiple regression analysis. The results revealed the following: 1) The condition of palliative care for cancer patients in overall, which was a clear policy and sufficient budget for management. 2) Current effectiveness of care and treatment and expected effectiveness. 3) The effectiveness of palliative care for cancer patients by organizational characteristics was not significantly different. 4) The factors of care characteristics and the availability of management factors together can explain the overall effectiveness of palliative care for cancer patients at 59.90%. 5) The 4 guidelines for the management to increase their effectiveness were 1) creating specialized unit for the cancer patients palliative care, 2) creating the team working process, 3) enhancing the palliative care process knowledge for the stakeholder, cancer patients and their relatives, as well as 4) creating the system and mechanism involved the stakeholder quality of life.